MENGGAGAS KURIKULUM MULOK TEROBOSAN BERBASIS KEARIFAN BUDAYA NUSANTARA (Rekonstruksi Pengalaman Sedulur Sikep Sukolilo, Pati, Jawa Tengah) - Said, Nur (JURNAL ISLAM NUSANTARA, 2017)
Initiated by none other than education to defend humanity as a whole through physical and psychological dimensions. Therefore, education can not be reduced merely to deliver students a mere material satisfaction, while the value immersiaal as social, spiritual and transcendental. Therefore, the curriculum should be developed on the basis of social conditions, culture and history which is held up the process of education or it is called place-based education. This brief paper will try to indigenous community "Sedulur sikep" perspective or better known as Samin in scrutinizing the school children which is not sensitive to social phenomena such as natural disasters and the environmental sustainability. Important message of this paper asserts that the most basic education is delivered into the individual learners who have senses of curiosity, so they still learn though it is complete / graduate school at their level. So awareness of lifelong learning woke up and could open eyes and mind to always seek and find wisdom so that the parts coming civilized community will wake up.